EFEKTIVITAS SENAM NIFAS TERHADAP INVOLUSI UTERUS PADA IBU NIFAS DI PUSKESMAS MUARA TELANG KABUPATEN BANYUASIN - Fatrin, Tiara; Aryanti, Aryanti; Sari, Yona; Permadi, Yan (Jurnal Kesehatan Abdurrahman, 2024)
One of the non-conventional therapies usually given to postpartum mothers to accelerate the reduction in uterine involution is postpartum exercise. Movements in postpartum exercises can train and tighten the abdominal muscles so that they can indirectly stimulate the uterine muscles to function optimally and prevent post-partum bleeding. The aim of this research is to determine the effectiveness of postpartum exercise on uterine involution in postpartum women at the Muara Telang Community Health Center, Banyuasin Regency. The research method used was a control group design approach. The population was all postpartum mothers totaling 40 people and a sample of 20 people, of which 10 cases and 10 controls used purposive sampling technique. The data analysis used was the Chi Square test. Research results: There was a difference in uterine involution before and after postpartum exercise, the pretest average value was 10.90 and the posttest average value was 3.50, whereas in the control cases on the first day and on the seventh day the average value was 11. 20 and an average value of 5.70, so there is a difference before and after giving postpartum exercises on uterine involution in postpartum mothers at the Muara Telang Community Health Center, Banyuasin Regency. It is hoped that postpartum mothers will increase their knowledge about the benefits of postpartum exercise.